Flexible Liquid Crystal Polymer based complementary split ring resonator loaded quarter mode substrate integrated waveguide filters for compact and wearable broadband RF applications (2014)
In this paper the flexible Liquid Crystal Polymer (LCP) substrate is used to implement broadband wearable/foldable conformal bandpass filters that use compact cavity resonators working under the principle of quarter mode substrate integrated waveguide (QMSIW), which features a 75% size reduction with respect to the conventional substrate integrated waveguide (SIW) counterpart. Further size reduction is realized with the use of a complementary split ring resonator (CSRR) metamaterial unit cell integrated with the QMSIW architecture. The resulting CSRR-loaded QMSIW cavity has its main resonance frequency below the quasi-TE0.5,0,0.5 resonance mode of the original QMSIW cavity due to the evanescent wave amplification phenomenon with CSRR loading. A low temperature surface micromachining process on the LCP and mechanical drilling of via holes are used for fabrication. The realized CSRR-loaded QMSIW cavity features a moderate quality factor (Q) that makes it useful for the design of bandpass filters with much broader fractional bandwidth (FBW) when compared to those using conventional SIW cavities. A 2nd order and a 3rd order surface micromachined Chebyshev BPFs are demonstrated for operation at a center frequency of 25.5 GHz. More than 11% FBW with an in-band return loss of better than 20 dB and an insertion loss of less than 1.5 dB, including transitions, are obtained for both filters. Theoretical analysis of the working principle is explained. Measured results are in good agreement with the 3D full wave structure simulations. © 2014 IEEE.